ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ðµ Ñ‡ÐµÑ€ÐµÐ½ÐºÐ¾Ð² Ð¿Ð»Ð¾Ð´Ð¾Ð²Ð¾-ÑÐ³Ð¾Ð´Ð½Ñ‹Ñ… ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€ - Gorbunov, L. V.; Shiyanova, T. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
It has been established that temperature, storage period, humidity, rates of cooling and thawing significantly affect viability of frozen-thawed cuttings. The found permissible values of humidity, parameters, providing maximal viability of birch, black currant berry, raspberry, cherry cuttings are 32–40; 40–50; 37–40; 33–45% within the positive range of temperatures and 14–28, 30–40, 23, 37% within the negative range. Decrease of humidity results in plasmolysis, and exceeding does in intracellular crystal-formation. During application of different regimens of drying and cooling with the rate of 0.1°C/hr down to –20°C with further plunging into liquid nitrogen the viability of frozen-thawed cuttings of currant berry and birch made 100%, 88% for raspberry and 57% for cherry.